Penerapan Sistem HVAC Efisien Energi melalui Edukasi dan Pendampingan pada Proyek Rumah Susun BIN-POLRI (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2025)
This community service activity aims to provide education and technical recommendations related to energy efficiency and thermal comfort in the BIN Apartment building through simulations using DesignBuilder software. The purpose of the activity is to analyze and optimize the building’s energy consumption and ensure thermal comfort for the residents. The simulation results show that the building's Energy Use Intensity (EUI) is relatively low for the residential category, based on calculations made by the BGH team. The air conditioning (AC) system in conditioned spaces meets the thermal comfort standards according to ASHRAE, ensuring comfortable living conditions in these areas. However, in unconditioned areas, such as the family room, the Predicted Mean Vote (PMV) value reaches 1.5 (hot), indicating thermal discomfort. To address this issue, mechanical ventilation is recommended, with the capacity to produce an average air velocity of at least 0.6 m/s, which will improve airflow and enhance thermal comfort. Alternatively, adding an additional AC unit can also be considered, though it would result in a 20% increase in energy consumption. The findings and recommendations of this activity are expected to provide valuable insights and assist partners in making informed technical decisions when designing efficient and comfortable HVAC systems for vertical state-owned residential buildings. Ultimately, this program aims to optimize both energy usage and comfort, contributing to sustainable building management practices in the future.